Characteristics and clinical course of thyroid abnormalities arisen in long term survivors of childhood cancer - Hye Young Jin; Jun Ah. Lee; Meerim Park; Dong-Eun Lee; Hyeon Jin Park (BMC, 2023)
Abstract Background Thyroid abnormality is a common late effect seen in childhood cancer survivors (CCSs). We analyzed the prevalence and risk factors of thyroid abnormalities based on diagnoses and treatment modalities in CCSs. Methods The medical records of 257 CCSs who were diagnosed with cancer less than 20 year of age were retrospectively reviewed. The median age was 11.8 years (0.1-19.8). The median follow-up period after completion of therapy was 9.6 years (5.0-19.5). Results Of 257 subjects, thyroid abnormalities were identified in 107 (41.6%). Sixty-five out of 257 (25.3%) had subclinical hypothyroidism, and 16 (6.2%) developed central hypothyroidism. Five CCSs (1.9%) had primary overt hypothyroidism. Five (1.9%) and 6 (2.3%) CCSs were diagnosed with autoimmune thyroiditis and thyroid cancer, respectively. Among the different diagnostic groups, thyroid abnormalities were frequent in the brain tumor or Hodgkin disease or nasopharyngeal cancer groups. CCSs who received irradiation directly or near hypothalamus-pituitary-thyroid (HPT) axis had more thyroid abnormalities compared to the rest CCSs (P < 0.0001). CCSs who were treated with SCT had an increased prevalence of thyroid abnormalities (60.5%) compared to the other CCSs (37.9%) (P = 0.0069). Forty-five (42%) of 107 subjects with thyroid abnormalities had normalized thyroid hormone levels at the last follow-up. Irradiation directly or near HPT axis were thought to be a predicting factor of persistent subclinical hypothyroidism. Conclusions Subclinical hypothyroidism was common in CCSs. CCSs with irradiation directly or near HPT axis were at risk for persistent thyroid dysfunction.